Penerapan Model Project Based Learning untuk Meningkatkan Hasil Belajar Siswa pada Mata Pelajaran IPA Kelas V SDN Potto Katillu - Lende, Trimurti Elvin; Lede, Yulius Keremata; Engge, Yohanes; Milla, Daindo (Lembaga Intelektual Muda (LIM) Maluku, 2025)
The aim of this research is to improve learning outcomes by using the project-based learning model for fifth-grade students at SDN Potto Katillu. The research method used is Classroom Action Research conducted in cycle 1 and cycle 2. The subjects of the research are 22 fifth-grade students. The data collection techniques used in this research are learning outcome tests and observations. The data analysis technique used is qualitative descriptive analysis. The students' learning outcomes showed improvement from cycle 1 to cycle 2. The learning outcomes in cycle I showed that the number of students who passed was 10 people (52.63%), while those who did not pass numbered 9 people (47.37%). In cycle II, there was an increase in the number of students who passed to 17 people (89.47%). Meanwhile, those who did not pass were 2 people (10.53%). Based on these research results, it can be concluded that the PjBL model applied was successful.